BS10 Canagliflozin, an SGLT2 inhibitor attenuates ischaemia/reperfusion injury in the non-diabetic heart. (May 2019) - Lim, Ven Gee; Arjun, Sapna; Bell, Robert; Yellon, Derek
Abstract : Introduction: Sodium-glucose linked cotransporter 2 (SGLT2) inhibition has been shown to have unexpected cardiovascular benefits in recent landmark outcome trials. We previously hypothesized that this is mediated through attenuation of ischaemia/reperfusion injury and have demonstrated significant attenuation of infarct size in both diabetic and non-diabetic animals, irrespective of glucose lowering. That the protection is not found in isolated heart led us to hypothesize that the cardioprotection is via a hormone-mediated mechanism that leads to receptor activated kinase activation and cytoprotection. Methods: Non-diabetic male Sprague-Dawley rats were fed either standard chow or canagliflozin-fortified diet for 24 hours. Blood samples were obtained (glucose, insulin, glucagon, β-hydroxybutyrate) before the hearts were harvested for Langendorff perfusion, subjected to 35 min regional ischaemia and either 5 min or 2 hour reperfusion for either signaling (Western Blot analysis) or infarct size assessment. Results: 24h oral canagliflozin led to a significant attenuation in myocardial infarct size (Control 62±5% vs Canagliflozin 45±4%, p=0.016), equivalent to that found following ischaemic conditioning (IPC, figure 1). Concomitant with this, we found that within the ischaemic myocardium (left ventricle [LV]), there was a significant increase in Akt and ERK (but not STAT3 phosphorylation), an augmentation absent in remote (right ventricular [RV]) myocardium (figure 2 ). Despite maintenance of serum glucose, there was no difference in circulating insulin or glucagon. Similarly, there was no significant chance in the ketone, β-hydroxybutyrate, suggesting that increased availability of ketones is an unlikely mechanism of cardioprotection in this model. Conclusion: Canagliflozin led to a reduction in myocardial infarct size with associated Akt and ERK phosphorylation (well-known mediators of cardioprotection). Pathway-specific inhibitors may help elucidate the causal role of Akt and ERK activation. Interestingly, circulating levels of insulin, glucagon, ketone and glucose did not seem to contribute to the observed cardioprotection. Further studies are vital to identify the hormone responsible for activating pro-survival pathways but our data highlights the potential use of SGLT2 inhibitors as a novel cardioprotective therapy in high-risk cardiovascular patients regardless of diabetic status. Conflict of interest: None